Influence of Nigerian Home Movies on the Behaviourial Disposition of Nigerian Youths - Micheal A. Nza-Ayang; Olimma Benedette Ngozi (MultiTech Publisher, 2023)
The study examines the impact of Nigerian home moves on Nigerian youth behavior, emphasizing the need for government intervention to restore order and preserve cultural values through education, mobilization, and entertainment. Negative attitudes because of violent movies Therefore, it is recommended that the abundance of local films undergo careful examination prior to production and distribution in order to have a positive influence on Nigerian society as a whole. The proliferation of local films is problematic. we used 200 respondents as our sample size drawn from our research production amuwo-Odofin Local Government Areas (Lagos) to test the variety of interest. Also the survey research method of data collection was employed to generate information on the impact of Nigerian home movies on the youth. Three hypotheses in chapter four, two of The impact of Nigerian home movies on youth was investigated using the survey research method of data collection. In chapter four, there were three hypotheses; two of them passed the test, and one failed due to the violence connected to certain house moves. Tables, straightforward percentages, etc. were used to present the analysisThe study explores the impact of Nigerian home movies on the behavioral patterns of young people in secondary schools and tertiary institutions in Amumo Odofin and Lagos.